Experience in the application of organ-preserving technologies in the treatment of patients with cervical pregnancy - M. S. Selikhova; M. A. Yakhontova; A. A. Smolyaninov (Лечащий Врач, 2023)
Currently, one of the topical topics in obstetrics and gynecology is the problem of ectopic pregnancy, which directly correlates with an increase in the incidence of inflammatory diseases of the pelvic organs. Ectopic pregnancy has both the most common forms (the location of the ovum in various parts of the fallopian tube) and rare variants (ovarian, abdominal and cervical). Until 2017, the diagnosis of progressive cervical pregnancy was a direct indication for volumetric organ-carrying surgery – extirpation of the uterus. Currently, in view of the availability of modern treatment protocols ("Procedure for the provision of medical care in the profile of≫ obstetrics and gynecology", No. 1130н, 2020 and clinical guidelines "Ectopic pregnancy", 2017), obstetricians-gynecologists have the opportunity of conservative treatment this pathology and the preservation of the reproductive health of patients. This article presents three clinical cases of the use of organ-preserving techniques in the treatment of progressive cervical pregnancy, which occurred in the gynecological department of the Volgograd Clinical hospital of emergency medical care No. 7. For the treatment of patients, modern medical and surgical techniques were used: the use of cytostatic drugs, ligation of the uterine arteries, followed by vacuum aspiration of the ovum and control hysteroscopy. The effectiveness of the treatment was assessed using ultrasound imaging methods and laboratory research methods (blood test for hCG). Thus, clinical practice confirms the feasibility and effectiveness of organ-preserving surgical interventions, as well as the use of drug (cytostatic) therapy in patients with a diagnosis of ectopic (including cervical) pregnancy. This modern approach will preserve the reproductive potential of young women, as well as reduce the risks of possible complications in the future.